대벌레(Ramulus mikado)에 대한 유기농업자재 6종과 녹강균(Metarhizium anisopliae)의 살충 효과 평가 - 정종국; Jong-kook Jung; 정복남; Bok-nam Jung; 이차영; Cha Young Lee; 김건희; Keonhee E. Kim; 김준헌; Junheon Kim; 이영수; Young Su Lee; et al. (한국산림과학회지, 2023)
2020~2021년 은평구 봉산, 의왕시 청계산 등지에서 돌발적으로 대발생하여 산림에 피해를 주었던 대벌레(Ramulus mikado)의 친환경 방제를 위해 시판 중인 유기농업자재 6종과 산림 내에서 자연폐사한 대벌레에서 분리한 녹강균(Metarhizium anisopliae)의 살충 효과를 검정하였다. 유기농업자재 중에서는 azadirachtin과 geraniol을 포함하는 식물성 오일 3종이 85.2~100%로 높은 치사율이 확인되었으며 이는 화학 살충제인 페니트로티온 유제와 유사한 수준이었다. 녹강균의 분생포자를 희석하여 대벌레의 몸에 직접 분주하거나 사육장 내에서 분무기로 살포한 경우 모두 수일 내 100% 사망하는 것을 확인하였다. 본 연구를 통해 확인된 유기농업자재 3종과 녹강균 등은 향후 친환경 방제제 선발 및 사용 시 우선적으로 고려할 수 있을 것이라 판단된다. Outbreaks of Ramulus mikado (Insecta: Phasmatodea: Phasmatidae) in the hilly areas of Mt. Bongsan, Mt. Cheonggye, and elsewhere in Seoul and Gyeonggi occurred from 2020 to 2021, causing serious defoliation. We evaluated the insecticidal effects of six eco-friendly organic materials and the insect-pathogenic fungus Metarhizium anisopliae against R. mikado. The fungus was isolated from naturally dead bodies of R. mikado in forest ecosystems. The results revealed that three eco-friendly organic materials containing azadirachtin or geraniol as active ingredients showed high mortality in the range of 85.2%-100%, which were rates similar to that of the chemical insecticide fenitrothion emulsifiable concentrate. All R. mikado adults that were sprayed with a conidial suspension of M. anisopliae at different concentrations were killed within a few days. In conclusion, three eco-friendly organic materials and M. anisopliae could be good alternatives to chemical insecticides.